Control of Structural and Electrical Properties of Indium Tin Oxide (ITO)/Cu(ln,Ga)Se-2 Interface for Transparent Back-Contact Applications - Son, Yu-Seung; Yu, Hyeonggeun; Park, Jong-Keuk; Kim, Won Mok; Ahn, Seung-Yeop; Choi, Wonjun; Kim, Donghwan; Jeong, Jeung-hyun (American Chemical Society, 2019)
Development of transparent-conducting oxide (TCO) back contact for Cu(In,Ga)Se-2 (GIGS) absorber is crucial for bifacial CIGS photovoltaics. However, inherent GaOx formation at the TCO/GIGS interface has hampered the photocarrier extraction. Here, by controlling the Na doping scheme, we show that the hole transporting properties at the indium tin oxide (ITO)/CIGS back contact can be substantially improved, regardless of the GaOx formation. Na incorporation from the glass substrate during the GaOx forming phase created defective states at the interface, which allowed efficient hole extraction from CIGS, while post Na treatment after GaOx formation did not play such a role. Furthermore, we discovered that an almost GaOx-free interface could be made by reducing the underlying ITO film thickness, which revealed that ITO/CIGS junction is inherently Schottky. In the GaOx-free condition, post-Na treatment could eliminate the Schottky barrier and create ohmic junction due to generation of conducting paths at the interface, which is supported by our photoluminescence analysis.
Keywords: FILM SOLAR-CELLS